Pubblicità, educazione e diritto in Kant - Perni, Romina (Studi e saggi, 2023)
The starting point is the conviction that publicity is central to Kantian political thought as part of the wider relationship between politics and morality. In this sense the book aims to outline subjective and objective limits of the public control of power, which must be structurally guaranteed from a juridical point of view and that citizens/subjects have to put into practice. But from a Kantian point of view publicity is also linked to education and to the public use of reason, that individuals must have the courage to realize. The individual dimension and the collective/institutional one are tightly linked to answer the question: according to Kant, is it possible an education to publicity?